Predictably irrational: assaying cognitive inflexibility in mouse models of schizophrenia - Brigman, Jonathan L.; Graybeal, Carolyn; Holmes, Andrew (Frontiers in Neuroscience, 2010)
The development of sophisticated, translatable mouse-based assays modeling the behavioral manifestations of neuropsychiatric diseases such as schizophrenia has lagged the advances in molecular and genomic techniques. Our laboratory has made efforts to fill this gap by investing in the development of novel assays, including adapting a touchscreen-based method for measuring cognitive and executive functions for use in mice. As part of these efforts, a recent study by Brigman et al. (2009) investigated the effects of subchronic phencyclidine (PCP) treatment on mouse touchscreen-based pairwise visual discrimination and reversal learning. Here, we summarize the results of that study and place them in the larger context of ongoing efforts to develop valid mouse ‘models’ of schizophrenia, with a focus on reversal learning and other measures of cognitive flexibility. Touchscreen-based systems could provide a tractable platform for fully utilizing the mouse to elucidate the pathophysiology of cognitive inflexibility in schizophrenia and other neuropsychiatric disorders.